2020
DOI: 10.1186/s12978-020-01004-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing contraceptive use or non-use among Aboriginal and Torres Strait Islander people: a systematic review and narrative synthesis

Abstract: Background The Australian population has an unmet need for contraception. However, evidence suggests contraceptive patterns of Aboriginal and Torres Strait Islander populations are unique. To tailor contraceptive services and meet the contraceptive needs of Aboriginal and Torres Strait Islander people, it is important to understand the contributing factors to contraceptive use and non-use. Methods This study aimed to systematically review and narratively synthesise the evidence exploring the factors influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
3
6
0
1
Order By: Relevance
“…Based on the study there are several factors that can influence mothers to use contraceptives, namely lack of knowledge and acceptance of wrong information related to the types of contraception available (Cohen et al 2017) (Coombe et al 2020) Another factor is the mother's shame to use existing contraceptives (Coombe et al 2020). This is in line with other studies which say that contraceptive use is influenced by several factors ranging from the individual, family, community level originating from the social environment and also the economic level (Chowdhury and Chakraborty 2017).…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Based on the study there are several factors that can influence mothers to use contraceptives, namely lack of knowledge and acceptance of wrong information related to the types of contraception available (Cohen et al 2017) (Coombe et al 2020) Another factor is the mother's shame to use existing contraceptives (Coombe et al 2020). This is in line with other studies which say that contraceptive use is influenced by several factors ranging from the individual, family, community level originating from the social environment and also the economic level (Chowdhury and Chakraborty 2017).…”
Section: Introductionsupporting
confidence: 64%
“…The high maternal mortality rate in Indonesia makes the government have a special strategy in reducing AKI, one of which is safe motherhood, which consists of four pillars, namely antenatal care, clean and safe delivery, essential obstetric services, and family planning (Edy 2018) . Family planning programs have an important role in reducing the risk of maternal death through delaying gestational age, spacing pregnancies, and preventing pregnancy (Coombe et al 2020) .…”
Section: Objective Why Is This Research Needed ?mentioning
confidence: 99%
“…2015; Coombe et al. 2020). Rather than having a single reason for contraceptive nonuse that fits neatly into the demand‐side or supply‐side buckets, it is likely that many women actually have a complex rationale for contraceptive nonuse that straddles both categories.…”
Section: Discussionmentioning
confidence: 99%
“…An agenda for future research would include following up with women who did not answer this question, using in-depth cognitive interviewing to better understand reasons for nonresponse. Additionally, many respondents to the DHS give only one reason for not using a method during the quantitative survey, in contrast to a wealth of evidence showing that reasons for contraceptive nonuse are manifold and rarely exist in isolation ( Brown and Guthrie 2010 ; Iuliano et al 2006 ; Cheung and Free 2005 ; Borrero et al 2015 ; Wu et al 2008 ; Adebowale and Palamuleni 2014 ; Ochako et al 2015 ; Coombe et al 2020 ). Rather than having a single reason for contraceptive nonuse that fits neatly into the demand-side or supply-side buckets, it is likely that many women actually have a complex rationale for contraceptive nonuse that straddles both categories.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that age , an education level (Blackstone, Nwaozuru, & Iwelunmor, 2017;, and social economic status Najafi-Sharjabad et al, 2013) affects contraceptive use. In addition, the sociocultural environment including ethnicity (Coombe et al, 2020), religion (Ayorinde et al, 2021;Hoga, Rodolpho, Sato, Nunes, & Borges, 2014;Olakunde et al, 2019), and habitat (Joshi et al, 2021) causes variations in contraceptive use rates. Therefore, understanding people's sociocultural backgrounds, particularly ethnicity and locality, is essential for designing and implementing effective family planning programs.…”
Section: Introductionmentioning
confidence: 99%